2023
DOI: 10.1021/acs.nanolett.2c03565
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Low-Voltage Hexagonal Boron Nitride Nonvolatile Switches for Millimeter-Wave Wireless Communications

Abstract: Recently, nonvolatile resistive switching memory effects have been actively studied in two-dimensional (2D) transition metal dichalcogenides and boron nitrides to advance future memory and neuromorphic computing applications. Here, we report on radiofrequency (RF) switches utilizing hexagonal boron nitride (h-BN) memristors that afford operation in the millimeter-wave (mmWave) range. Notably, silver (Ag) electrodes to h-BN offer outstanding nonvolatile bipolar resistive switching characteristics with a high ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…The cross-section of an hexagonal borond nitride RF switches, similar as the ones demonstrated in the literature [7], [9], [11], is shown in Fig. 2(a).…”
Section: B Dynamic Responsementioning
confidence: 61%
See 1 more Smart Citation
“…The cross-section of an hexagonal borond nitride RF switches, similar as the ones demonstrated in the literature [7], [9], [11], is shown in Fig. 2(a).…”
Section: B Dynamic Responsementioning
confidence: 61%
“…The return loss, an important factor for RF switches [24], not reported experimentally for any of the devices under study [6], [7], has been calculated here by using Eq. (11). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The R HRS / R LRS ratio can be tuned as the current compliance changes with high dynamic ranges, as reported for the realization of programmable memresistors. [ 39,40 ] LRS modulation is possible for more than one order of magnitude, as shown in Figure 3h, showing the multilevel memory capability of the GaN NW device by tuning the compliance currents. To investigate the data loss performance in the ON and OFF states, the retention was measured at a reading voltage of 0.5 V (Figure 3i).…”
Section: Resultsmentioning
confidence: 97%
“…Yang et al reported radiofrequency switching in the millimeter-wave range using a hexagonal boron nitride memristor with the Ag/h-BN/Ag structure. 119 This memristor showed excellent nonvolatile bipolar resistanceswitching characteristics, including a high on/off ratio (B10 11 ) and a low switching voltage (o0.34 V). It also exhibited pulseswitching characteristics when set at high speed with a very low power of 0.23 W and energy consumption of 1.2 nJ.…”
Section: Hexagonal Boron Nitride (H-bn)mentioning
confidence: 96%